2020
DOI: 10.1016/j.annemergmed.2020.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound for COVID-19 Evaluation in the Emergency Department: Is It Feasible?

Abstract: Funding and support: By Annals policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On the other hand, it has variable sensitivity/specificity depending on the setting in which it is used (e.g. the emergency department versus critical care) [32][33][34] and facilities and expertise in this imaging modality are less than they are for CTPA in most UK hospitals, which may prevent more widespread use [35][36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has variable sensitivity/specificity depending on the setting in which it is used (e.g. the emergency department versus critical care) [32][33][34] and facilities and expertise in this imaging modality are less than they are for CTPA in most UK hospitals, which may prevent more widespread use [35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of feasibility, Wolfshohl et al [38] conducted a survey on emergency physicians which suggested the majority were not prepared to perform LUS in emergency settings because of lack of targeted training despite their awareness of its superior diagnostic performance. In contrast, Narinx et al [26] reported a more positive experience in their study, which agrees with our experience, in which LUS was a useful, rapid, and safe tool in the ER.…”
Section: Discussionmentioning
confidence: 99%